An investigational study on Pre and post-stabilization behaviour of Lime stabilized Expansive soil admixed with palm kernel ash. Issue 1 (1st January 2023) - vijayan, Dhanasingh sivalinga; Devarajan, Parthiban; Sanjay Kumar, R; Ajith Kumar, V; Raj kumar, S; Rahman, Shaik Habibur
Abstract: In geotechnical engineering, soils that can shrink and swell quickly are always thought to be more sensitive than other types of soil. Most of the research on how to improve the engineering behaviour of expansive soil and make it more stable has already been done. The main goal of the project is to find a better way to treat large amounts of expansive soil with low-cost material and to analyse the modification of engineering properties of soil such as compressive strength and Atterberg limit. In this study, lab results on soils with a lot of space that were treated with cheap ingredients like lime and palm kernel ash are used. This study looks at the results of the unconfined compression test (UCC), liquid limit, plastic limit, shrinkage limit, and plasticity index for expansive clays mixed with different amounts of lime and palm kernel ash. Based on the result, it was found that the addition of 5% lime with 0.25% of PKA increased the UC strength of soil from 1418.17 kN/m 2 to 1537.97 kN/m 2 at 28 days of curing. Similarly, due to increase in the percentage of palm kernel ash with lime treatment has decreased the rate of atterberg limit except for the plastic limit. In the case of plastic limit, the addition of 0.25% of palm kernel ash was recommended. Finally, it was concluded that the addition of palm kernel ash with lime was advisable for minor soil stabilization work.